MORPHOLOGICAL PARAMETERS OF SPLEEN AND THYMUS OF THE RATS AFTER THE INFLUENCE OF SALINE EXTRACTS HIRUDO VERBANA - Aminov, R.F.; Syrtsov, V.K.; Fedosieieva, O.V.; Frolov, A.K. (World of Medicine and Biology, 2019)
The work was aimed to investigate the morphological parameters of the spleen and thymus of rats against the background of influence of the saline extract Hirudo verbena. The females were injected intraperitoneally with a standardized salt extract from the bodies of a medical leech, twice before mating with males and twice after it. On feeding offspring, on the 60th day after the last injection of the substance, the females and their offspring in dynamics, on the 15th, 30th, 45th and 60th days of the postembryonic ontogenesis, were decapitated. We analyzed the white pulp of the spleen - the area and diameter of lymphoid follicles, central arteries and the number of lymphocytes per a unit area (400 μm2) in lymphoid follicles, in the thymus - the number of lymphocytes per a unit area, both in the cortical and brain substance. Under the influence of biologically active substances of a medicinal leech in the white pulp of the spleen, the sizes of lymphoid follicles and central arteries grow, the number of lymphocytes per a unit area (400 μm2) of the lymphoid follicle grows, and the number of cells per a unit area in the thymus of the offspring, both in the cortical and brain substance areas (400 μm2), there is a predominance of cortical substance over the medulla. The study revealed a stimulating effect of the Hirudo verbana salt extract on immunogenesis in the central and peripheral organs of the immune system.
Keywords: medicinal leech; hirudotherapy; morphogenesis; spleen; thymus